2020
DOI: 10.1002/slct.202003343
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence In Situ Hybridization of 16S rRNA in Escherichia coli Using Multiple Photo‐Cross‐Linkable Probes

Abstract: RNA forms various secondary structures depending on its sequence in cells; the influence of secondary structures must be considered when detecting, regulating, or manipulating RNA. In this study, we utilized the cooperativity of multiple photo‐cross‐linkable assistant probes to evaluate photo‐cross‐linking for RNAs with complex secondary structures. We succeeded in increasing the fluorescence intensity 39.9 times in the region where detection was difficult owing to the formation of a complex secondary structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…However, these photo-crosslinkers can only crosslink to the counter base if it is adjacent to the 5 0 -side (À1) position to the crosslinker-containing base (5 0 -nXn-3 0 and 5 0 -Ynn-3 0 where X is the crosslinker-containing base and Y indicates the position of the crosslinked pyrimidine). 8,14,[106][107][108][109][110][111][112] Fujimoto et al reported that the rate constant of the photocrosslinking reaction of CNV D is 0.106 s À1 which is comparable to CNV K (0.059 s À1 ). Within the same sequence, psoralen showed a much slower photo-crosslinking rate (0.003 s À1 ) using the same wavelength (365 nm).…”
Section: Carbazolementioning
confidence: 99%
See 2 more Smart Citations
“…However, these photo-crosslinkers can only crosslink to the counter base if it is adjacent to the 5 0 -side (À1) position to the crosslinker-containing base (5 0 -nXn-3 0 and 5 0 -Ynn-3 0 where X is the crosslinker-containing base and Y indicates the position of the crosslinked pyrimidine). 8,14,[106][107][108][109][110][111][112] Fujimoto et al reported that the rate constant of the photocrosslinking reaction of CNV D is 0.106 s À1 which is comparable to CNV K (0.059 s À1 ). Within the same sequence, psoralen showed a much slower photo-crosslinking rate (0.003 s À1 ) using the same wavelength (365 nm).…”
Section: Carbazolementioning
confidence: 99%
“…Incorporating multiple crosslinkers could help increase the sensitivity of FISH by 40-fold in the region where detection was difficult due to complex secondary structures using conventional FISH. 112 Fujimoto group reported the use of CNV K photocrosslinking in antisense DNA technology: photocrosslinkable antisense oligonucleotides containing CNV K can regulate GFP expression in a sequence-specic manner only aer 10 s photocrosslinking with 365 nm light in HeLa cells. In a recent study, they investigated and compared the photo-crosslinking rate and its inhibitory effect including CNV D, CNV K, and psoralen on gene expression.…”
Section: Carbazolementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the reaction rate 46 was further improved by changing the sugar structure and the wavelength of the forward and reverse reactions 47 was lengthened by changing the vinylcarba-zole base structure. This type of crosslinking has been used for many applications, such as the inhibition of translation, 48,49 RNA editing, 50,51 RNA fluorescence in situ hybridization, [52][53][54] functional gel material engineering, 55 and DNA origami. 56 In DNA nanotechnology, the photoreversible crosslinking property of CNV K is one of the advantages of creating smart materials.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…1(a),(b)]. The results obtained using intracellular antisense nucleic acids 19 and the fluorescence in situ hybridization (FISH) method 20 have proven that the photochemical manipulation of DNA or RNA can be performed at the nanoscopic scale even in cells, which are more complicated systems. We also investigated DNA nanotechnology and succeeded in changing liposome membrane structures using DNA tiles by aggregation negative charges resulting from the DNA aggregation at the liposome surface.…”
Section: Introductionmentioning
confidence: 99%